Pembauran Masyarakat Pendatang dengan Masyarakat Lokal Suku Mentawai - Heribertus Samarurok; Ideal Putra; Nurman Nurman (Journal of Civic Education, 2023)
Assimilation is a sociocultural phenomenon that manifests in heterogeneous societies where diverse cultural backgrounds converge. The current research delves into the assimilation dynamics between immigrant communities and the indigenous Mentawai tribes in Muara Siberut Village, Mentawai Islands Regency. The process of assimilation is facilitated through the utilization of the local language as a means of communication, engagement in cultural activities, and inter-ethnic marriages. Employing a descriptive qualitative approach, this study involves participants from immigrant communities, local communities, and traditional institutions. The findings indicate a harmonious assimilation process between the immigrant communities and the local Mentawai community, characterized by the preservation of their respective local wisdom values that have facilitated assimilation over an extended period of time.